TIGKAT KESEJAHTERAAN RUMAH TANGGA PEKERJA INDUSTRI MEBEL DI KOTA BUKITTINGGI - anisa anis nisa; Sri Mariya (JURNAL BUANA, 2025)
The purpose of this study is to determine the condition and welfare status of furniture industry workers and find out the distribution of industry in the city of Bukittinggi in 2023. Descriptive and quantitative research is conducted using interview methods in this type of research. Based on the data obtained from the interview results, it is known that there are 5 families (14.70%) including prosperous families 1, 9 families (26.47%) including prosperous families II, 12 families (35.29) including prosperous families III, and 8 families (23.52%) including prosperous families III plus.2). Based on the analysis of the nearest neighbors carried out at the furniture industry site in the city of Bukittinggi, it is classified as a random distribution pattern with a T index value of 0.834638